Correlation Between Customer Satisfaction, Customer Engagement, and Customer Loyality of D'Cost Seafood Restaurant - Sihotang, David CUH; Wandebori, Harimukti (Journal of Business and Management, 2014)
Seafood was one of the favourite consumption for Indonesian. Indonesia was the country with wide ocean teritory. It made Indonesian easy to make seafood for consumption. Seafood restaurant took part to deliver the best seafood that Indonesian needs. One of the seafood restaurants named D’Cost Seafood restaurant. D’Cost had more than fifty branches all over Indonesia. There were other seafood restaurants that compete with D’Cost. It was important for D’Cost Seafood to mantain their customers with their service quality, price, and product quality. It helped D’Cost improve customer satisfaction that correlated with customer engagement and customer satisfaction.Service quality was divided into five dimensions. Those were reliablity, assurance, tangible, empathy, and responsiveness. Those five would affect customer satisfaction. Customer satisfaction was affected by service quality, price, and product quality. Customer satisfaction correlated with customer engagement and customer loyalty.Customers would give scores to D’Cost Seafood restaurant with the questionnaire. The questionnaire would be tested by validity and reliability test. Questionnaire result would give customers description and score about service quality, price, product quality, customer satisfaction, customer engagement, and customer loyalty. From the questionnaire result there would be the correlation between each variables. It also tested the importance of each statements that would be defined by importance performance analysis.D’Cost Seafood customers were dominated by 17-25 year old customers, bachelor degree customers, customers with Rp 1,000,000 to Rp 2,000,000 expenditures, Bandung customers, customers that friends became their references, and customers with price as a reasons. D’Cost customers satisfaction result indicated that customer satisfaction based on service quality, price, and product quality relatively high. It means customers feel satisfied enough with service quality, price, and product quality of D’Cost Seafood restaurants. The correlation between customer satisfaction, customer engagement, and customer loyalty also strong. It indicated strong correlation between each dimennsion. Keywords : service quality, customer satisfaction, customer engagement, customer loyalty, D’Cost Seafood restaurant